Immobilization of manganese in solution and soil contaminated with trivalent chromium using biochars - Hyo Kyung Jee; Han Na Kim; Jin Hee Park (Applied Biological Chemistry)
Abstract Mn (manganese) exists in various oxidation states in soil, and Mn2+ is the most mobile species of Mn, which is toxic to plants and restricts their growth. When soil is contaminated with trivalent chromium (Cr3+), Mn oxides in the soil are reduced to Mn2+ by oxidizing Cr3+ while oxidized Cr is subsequently reduced back to Cr3+ by organic matter in soil, leaving Mn2+ and Cr3+ in the soil. Therefore, the objective of this study was to immobilize Mn2+ without altering the Cr species in the soil and to evaluate the effectiveness of biochar treatment in immobilizing both Mn2+ and Cr³⁺ in Cr³⁺-contaminated soil. Biochars derived from different sources including rice bran (RB), chicken manure (CM) and cow manure (WM) were tested for Mn adsorption and the chicken manure derived-biochar showed the highest removal efficiency (100%) for Mn in Mn solution. Moreover, 100% of both Mn²⁺ and Cr³⁺ were removed in Mn²⁺ and Cr³⁺ mixed solution without oxidizing Cr3+. In Mn2+ and Cr3+ mixed solution, initially 1.7% of Cr³⁺ was oxidized to Cr⁶⁺ by Mn, which was subsequently reduced back to Cr³⁺ by biochar, leading to its complete adsorption. In Cr3+ spiked soils treated with 5% and 10% CM biochar, bioavailable Mn and Cr concentrations were significantly reduced. Therefore, biochar is a promising amendment for reducing the bioavailability of Mn and Cr limiting Cr3+ oxidation in Cr3+ contaminated soils.